2022
DOI: 10.1021/acs.jafc.2c05881
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Key Odorants in Large-Leaf Yellow Tea (Camellia sinensis) by Application of the Sensomics Approach

Abstract: Large-leaf yellow tea (LYT) is a yellow tea product with a specific aroma characteristic and is enjoyed with increasing enthusiasm in China. However, its key odorants are still unknown. In this study, 46 odorants in the headspace and vacuum-distillate of the tea infusion were identified via aroma extract dilution analysis. Sixteen compounds were newly found in LYT infusion. They were present in the highest flavor dilution factors together with 2-ethyl-3,5-dimethylpyrazine. All odorants were quantitated to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…SCZ also contained a high proportion of alcohols (28%); however, unlike the other two varieties, heterocyclics comprised 32% of the total volatile content in QTZ, whereas alcohols comprised only 15%. Most heterocyclics are reported to have a roasted odor ( Zhai et al, 2023 ); hence, the high concentration of heterocyclics is probably responsible for the relatively high score for “roasted” in QTZ.…”
Section: Resultsmentioning
confidence: 99%
“…SCZ also contained a high proportion of alcohols (28%); however, unlike the other two varieties, heterocyclics comprised 32% of the total volatile content in QTZ, whereas alcohols comprised only 15%. Most heterocyclics are reported to have a roasted odor ( Zhai et al, 2023 ); hence, the high concentration of heterocyclics is probably responsible for the relatively high score for “roasted” in QTZ.…”
Section: Resultsmentioning
confidence: 99%
“…Coumarin has been detected in several tea categories, including green tea, black tea, yellow tea, and oolong tea. , Fresh tea leaves contain glycosidic aroma precursors of coumarin, which can be hydrolyzed to release the free-from coumarins during tea processing . It is well-known that fungi can produce a large number of extracellular enzymes, in which glycosidase can promote the glycoside-binding hydrolysis of coumarin precursors. Thus, it was speculated that the significant increase of coumarin content may result in the enhancement of flowery aroma in the FT.…”
Section: Resultsmentioning
confidence: 99%
“…Research has demonstrated that 2-methylbutanal, dimethyl sulfide, 2-ethyl-6-methylpyrazine, trimethylpyrazine, and 2-ethyl-3,5-dimethylpyrazine are the key odorants of the unique aroma in large-leaf yellow tea through aroma recombination and omission tests. 14 (E)-β-Ionone, geraniol, and (E,E)-2,4-heptadienal have been identified as the key odorants for the floral aroma properties of extra-virgin Lu'an Guapian through addition tests. 15 Many studies have been conducted on volatile compounds in fu brick tea and fermented tea by single E. cristatum, but the key odorants of fungal-flowery aroma and their key odorants are unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large yellow tea (LYT), a unique slightly fermented tea, is one of the six major categories of traditional tea (Camellia sinensis) processed in China which has gained increasing popularity in recent years owing to its pleasant toasty flavor and health-promoting functions, including anti-hyperglycemic, anti-hyperlipidemic, anti-inflammatory, and antiobesity. 9,10 Our previous studies reported that water extraction of LYT has remarkably attenuated macrophage-related chronic inflammation and metabolic syndrome in HFD-induced obese mice. 11 Recently, we obtained homogeneous polysaccharides (LYPs) from LYT with a known structure and a strong activity to promote the M2 polarization of macrophage in vitro cocultures.…”
Section: Introductionmentioning
confidence: 99%